(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Winaya A, Maftuchah, Nicolas CM, Prasetyo D. 2020. Morphometric variations of Asian Common Palm Civet (Paradoxurus Hermaphroditus, Pallas 1777) from Bali Island, Indonesia as the basis of morphometrics diversity data. Biodiversitas 21: 1027-1034. Asian Common Palm Civet (Paradoxurus hermaphroditus, Pallas 1777) is one of the small carnivores that also lives in Bali island, Indonesia. Civets can process coffee beans by fermenting them in the digestive tract, so the coffee beans have a unique aroma. This coffee product, commonly known as Kopi Luwak, is the most expensive type of coffee in the world. The purposes of this study were to obtain the morphometric variations, genetic diversity, and genetic relationship of Bali civets. In this study, we involved 73 civets from four different areas (Bangli, Tabanan, Gianyar, and Denpasar) of Bali Islands, Indonesia. The quantitative character was the body size of animals, and the qualitative character was their hair color. The body size among populations was not significantly different (P>0.05). The complete canonical structure analysis showed that tail length (1.04) and body length (0.76) in canonical 1 and body height (0.96) and head width (0.94) in canonical 2 could be used as a group differentiator. The genetic distance among Bali civets was categorized as close except Bangli civets having far distance than others.